Faithful transformations: Islamic self-help in contemporary Singapore - Jamil, Nurhaizatul Jamila (Dissident feminisms, 2025)
"Malay Muslim women in Singapore cultivate piety by attending popular Islamic self-help classes. Nurhaizatul Jamil's ethnographic study offers an interdisciplinary analysis of this phenomenon. The Islamic self-help classes in this book exist at the nexus of sacred texts, aphorisms, and social media engagements, scaffolded by the neoliberal economy that shapes idealized Muslim subjectivities. Within a context whereby the Singapore state discursively frames Malayness in terms of cultural deficiency, Malay Muslim women's inward focus on transformative ethics rather than societal change underscores the appeal of gendered pious self-help discourses. At the same time, Jamil's referencing of Black, Indigenous, and Ethnic studies offers a compelling analytical frame that places affective transformation within the context of racial capitalism, historical trauma, and embodied healing. A provocative and rich ethnography, Faithful Transformations tells the stories of Malay Muslim women desiring piety and self-improvement as minoritized subjects in contemporary Singapore while exploring the limitations of self-care"--